The RED experiment: an assessment of boundary layer effects in a trade winds regime on microwave and infrared propagation over the sea - Tsintikidis, Dimitris, author; Terrill, Eric, author; Smith, Michael, author; Reising, Steven, author; Reid, Jeffery S., author; Moerman, Marcel, author; Khelf, Djamal, author; Hristov, Tihomir, author; Friehe, Carl, author; Frederickson, Paul, author; Doss-Hammel, Stephen, author; Dion, Denis, author; et al. (Colorado State University. Libraries, 2004)
The Rough Evaporation Duct experiment aimed to see if the effects of ocean waves account for errors in modeling the ranges at which radar and infrared can detect low-flying targets.